2007
DOI: 10.1109/tasc.2007.898910
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Micron Non-Superconducting Deposits That Fail to Act as Pinning Centers in Textured YBCO Superconductor

Abstract: A conundrum is observed where one type of small, non-superconducting particles fails to provide pinning, in textured YBCO superconductor, while other non-superconducting particles of comparable size and number density, pin very well. Pinning centers in high temperature superconductors (HTS) have been shown to greatly enhance critical current density ( ). An experiment was performed in which large grain YBCO doped with uranium (U), but no platinum (Pt), was produced. Profuse deposits of a U-Y-Ba-O compound were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In an earlier study of uranium-doped, Pt-free YBCO, similar surprising results of B TRAP were found [8]. U-doped, Pt-free melt-textured YBCO samples contained profuse sub-micrometer sized deposits of a U-Y-Ba-O compound.…”
Section: An Earlier Experiments With Uranium-doped Pt-free Samplessupporting
confidence: 75%
See 2 more Smart Citations
“…In an earlier study of uranium-doped, Pt-free YBCO, similar surprising results of B TRAP were found [8]. U-doped, Pt-free melt-textured YBCO samples contained profuse sub-micrometer sized deposits of a U-Y-Ba-O compound.…”
Section: An Earlier Experiments With Uranium-doped Pt-free Samplessupporting
confidence: 75%
“…T C is defined as the midpoint of the temperature transition. In all samples measured, the T C is determined to be between 90 K and 91 K. The estimated error in our T C measurement is ± 0.5 K. With the samples being large, the value obtained for T C is rather typical for bulk YBCO superconductors [8][9]. The T C transition of all samples appears to be sharp.…”
Section: Critical Temperature (T C )mentioning
confidence: 56%
See 1 more Smart Citation
“…These are Pt-free deposits, and are the main subject of this report. As described in detail later in this report, the Ptfree deposits were studied and found to be of composition [12]:…”
Section: Introductionmentioning
confidence: 91%